T‐Hg2+‐T‐based satellite structured surface enhanced Raman scattering sensor for Hg2+ detection. (3rd July 2018) - Sun, Zhenli; Du, Jingjing; He, Kebin; Jing, Chuanyong
Abstract: Mercury ion (Hg 2+ ) exposure is a threat to human health. We report a plasmonic core‐satellite Fe3 O4 @SiO2 ‐Au (FA) hetero nanostructure for Hg 2+ detection using surface enhanced Raman scattering based on the T‐Hg 2+ ‐T strategy. The FA nanostructure was functionalized by a DNA aptamer, which was designed with Cy5 at the 5′ end, and used as a Raman reporter to specifically bind to Hg 2+ ions. In the presence of Hg 2+, DNA formed a hairpin structure, bringing Cy5 close to the FA hotspots region, thus generating an enhanced Raman signal. The T‐Hg 2+ ‐T complex formed the basis for the determination of trace Hg 2+ with a detection limit lower than 5 × 10 −9 M, and the influence of other metal ions was found to be negligible. With high selectivity, sensitivity, and recyclability, this FA‐DNA surface enhanced Raman scattering platform is a promising tool for field monitoring of Hg 2+ ions. Abstract : A simple, rapid, and sensitive surface‐enhanced Raman scattering nanosensor for the detection of Hg 2+ was developed on the basis of DNA‐functionalized Fe3 O4 @SiO2 ‐Au (FA) with a satellite structure. With high selectivity and recyclability, this FA‐DNA surface‐enhanced Raman scattering platform is a promising tool for field monitoring of Hg 2+ ions.